Implementasi Pendidikan Multikultural Melalui Kegiatan Kirab Budaya di Pondok Pesantren Wali Songo Ngabar Ponorogo - Umro'atin, Yuli (Proceedings of Annual Conference for Muslim Scholars, 2023)
Multicultural education seeks to teach diversity, one of which is through Islamic boarding school culture in the form of Islamic boarding school rules, habits or routine activities. Research objective: to analyze a planning, implementation and evaluation process of multicultural education at the Wali Songo Islamic Boarding School Ngabar Ponorogo. Qualitative research method with case studies. Research results: Multicultural education planning through working meetings at beginning of new school year; the implementation of Multicultural education is determined and implemented in the forum for introducing new students (ta'aruf) at the Khutbatul Iftitah or commonly referred to as the introduction week for new students at the Wali Songo Ngabar Islamic boarding school, precisely after the end of the Ramdhan and Shawwal holidays; The evaluation process is carried out at every leadership meeting and institutional meeting. The planning, implementation and evaluation process is part of the management tasks of Islamic education, both formal and non-formal, and within the scope of Islamic boarding schools. Multicultural education in Islamic schools is education for cultural diversity which has the urgency of implementing an attitude of tolerance and mutual respect for differences.